Feasibility and Therapeutic Potential of Combined Peptide Receptor Radionuclide Therapy With Intensive Chemotherapy for Pediatric Patients With Relapsed or Refractory Metastatic Neuroblastoma. (July 2021) - Fathpour, Gholamreza; Jafari, Esmail; Hashemi, Arman; Dadgar, Habibollah; Shahriari, Mahdi; Zareifar, Soheila; Jenabzade, Ali Reza; Vali, Reza; Ahmadzadehfar, Hojjat; Assadi, Majid
Abstract : Background: Recent evidence has demonstrated high expression of somatostatin receptors in neuroblastoma (NB) cells. Because of this, we endeavored to evaluate the diagnostic performance and clinical efficacy of 68 Ga-DOTATATE PET/CT and peptide receptor radionuclide therapy (PRRT) using 177 Lu-DOTATATE combined with chemotherapy in pediatric NB patients. Patients and Methods: In total, 14 pediatric patients with histopathologically confirmed NB underwent 68 Ga-DOTATATE PET/CT. Among them, the patients who were refractory or relapsed after therapy with 131 I-MIBG and had intensive uptake of 68 Ga-DOTATATE were referred for PRRT using 177 Lu-DOTATATE. Treatment response based on follow-up imaging was classified into complete response, partial response, stable disease, and progressive disease. After each cycle of PRRT, laboratory tests were performed for evaluation of hematological, renal, and hepatic toxicities. The CTCAE (Common Terminology Criteria for Adverse Events; version 4.03) was used for grading adverse event. Curie score and International Society of Pediatric Oncology Europe Neuroblastoma score were used for semiquantitative analysis of scans of patients who underwent PRRT. In addition, overall survival was calculated as the time interval between the date of the first cycle and the end of follow-up or death. Results: Overall, 14 refractory NB children including 7 boys and 7 girls with a median age of 5.5 years (ranged from 4 to 9) underwent 68 Ga-DOTATATE PET/CT. PET/CT was positive in 10/14 patients (71.4%), and the median number of detected lesions in positive patients was 2 (range, 1–13). Of 14 patients, 5 patients underwent PRRT, including 3 boys and 2 girls. A total of 19 PRRT cycles and 66.4 GBq 177 Lu-DOTATATE were given. Among these 5 patients, 2 showed an initial complete response, which relapsed a few months later, 1 showed a partial response, and 2 showed progressive disease. According to the Kaplan-Meier test, the overall survival was estimated at 14.5 months (95% confidence interval, 8.9–20.1). In evaluation of PRRT-related toxicity according to the CTCAE, 4 patients showed grade 1, and 1 showed grade 2 leukopenia. Two patients showed grade 1, and 2 others showed grade 2 anemia. Two patients showed grade 1, and 3 patients showed grade 2 thrombocytopenia. Serum creatinine in 1 patient increased to grade 1. Conclusions: Combination of 177 Lu-DOTATATE with chemotherapeutic agents might achieve worthwhile responses with low toxicity, encouraging survival in NB patients who have relapsed or are refractory to conventional therapy, including 131 I-MIBG therapy. Imaging with 68 Ga-DOTATATE PET/CT in such patients has a relatively high detection efficacy, demonstrating its potential use as an alternative imaging tool to conventional modalities such as 123 I/ 131 I-MIBG. However, further well-designed trials are highly warranted.